Neuronal selectivity of botulinum neurotoxins. (30th April 2020) - Poulain, Bernard; Lemichez, Emmanuel; Popoff, Michel R.
Abstract: Botulinum neurotoxins (BoNTs) are highly potent toxins responsible for a severe disease, called botulism. They are also efficient therapeutic tools with an increasing number of indications ranging from neuromuscular dysfunction to hypersecretion syndrome, pain release, depression as well as cosmetic application. BoNTs are known to mainly target the motor-neurons terminals and to induce flaccid paralysis. BoNTs recognize a specific double receptor on neuronal cells consisting of gangliosides and synaptic vesicle protein, SV2 or synaptotagmin. Using cultured neuronal cells, BoNTs have been established blocking the release of a wide variety of neurotransmitters. However, BoNTs are more potent in motor-neurons than in the other neuronal cell types. In in vivo models, BoNT/A impairs the cholinergic neuronal transmission at the motor-neurons but also at neurons controlling secretions and smooth muscle neurons, and blocks several neuronal pathways including excitatory, inhibitory, and sensitive neurons. However, only a few reports investigated the neuronal selectivity of BoNTs in vivo. In the intestinal wall, BoNT/A and BoNT/B target mainly the cholinergic neurons and to a lower extent the other non-cholinergic neurons including serotonergic, glutamatergic, GABAergic, and VIP-neurons. The in vivo effects induced by BoNTs on the non-cholinergic neurons remain to be precisely investigated. We report here a literature review of the neuronal selectivity of BoNTs. Highlights: - Botulinum neurotoxins are potent toxins that induce flaccid paralysis and inhibition of secretions. - Botulinum neurotoxins recognize not only cholinergic neurons but a wide variety of neuronal cells. - Botulinum neurotoxins inhibit the neurotransmission in motorneurons but also in sensory neurons.